Exploration of batik lukis motifs as a medium of art communication in Pahang - Sharulnizam Ramli,; Mohd Khairul Azahari Abdul Rani,; Zarlina Mohd Zamari, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Malaysian societies are more familiar with batik which hails from Kelantan and Terengganu. They know very little about batik from Pahang which is often more revered for its traditional craft product such as ‘tenun Pahang’(woven fabric). In other words, Malaysians are oblivious to the uniqueness of batik lukis from Pahang since much information about it offers only a general description. Based on this understanding, the present qualitative research is carried out through a case study method to explore and comprehend the process of Pahang batik lukis motif’s production from the perspectives of idea generation, practitioners, expression, representation, environment, creativity and aesthetics in order to delve deeper into the art behind the creation of batik lukis in Pahang as it is a Malay art heritage which must be conserved.